Clinical Review of Microbial Corneal Ulcers Resulting in Enucleation and Evisceration in a Tertiary Eye Care Center in Hungary - Gábor Tóth; Milán Tamás Pluzsik; Gábor László Sándor; Orsolya Németh; Olga Lukáts; Zoltán Zsolt Nagy; Nóra Szentmáry (Journal of Ophthalmology)
Purpose. To analyse the clinical and microbiological characteristics and preexisting ophthalmic and systemic conditions of infectious keratitis resulting in enucleation/evisceration in a large tertiary referral center in a developed country (Hungary) over a period of 12 years. Patients and Methods. A retrospective review of enucleated/eviscerated eyes undergoing surgery between 2007 and 2018 at the Department of Ophthalmology of Semmelweis University, Budapest, Hungary, with infectious keratitis as the primary indication for enucleation or evisceration. For each subject, clinical history, B-scan ultrasound report, and microbiological analyses were reviewed. Results. There were 48 enucleated/eviscerated eyes from 47 patients (29 females (61.7%), age at the time of surgery 66.4 ± 18.5 years). Indication for surgery was hopeless, unmanageable keratitis (62.5%), and keratitis with endophthalmitis (37.5%). The most common preexisting ophthalmic conditions were previous cataract surgery (60.4%), previous therapeutic penetrating keratoplasty (PKP) (56.3%), corneal perforation (52.1%), glaucoma (41.7%), and long-term topical steroid usage (31.3%). In order to treat keratitis, before enucleation or evisceration, 20 eyes (41.7%) underwent PKP, 12 eyes (25.0%) amniotic membrane transplantation, 8 eyes (16.7%) conjunctival autograft transplantation, 6 eyes (12.5%) tarsorrhaphy, and 4 eyes (8.3%) vitrectomy to salvage the eye prior to the final treatment of enucleation or evisceration. The most frequent preexisting systemic diseases were hypertension (62.5%), cardiac disease (20.8%), diabetes mellitus (20.8%), and rheumatoid arthritis (14.6%). Staphylococcus aureus (17.0%) and Propionibacterium acnes (12.8%) were the most commonly isolated gram-positive bacteria, and Pseudomonas aeruginosa was the most frequently isolated gram-negative pathogen bacterium (10.6%). Six globes (12.5%) had positive fungal cultures (1 case of Candida albicans, Candida parapsilosis, Trichosporon inkin, Acremonium sp., Fusarium sp., and Penicillium sp.). Conclusions. Staphylococcus aureus, Propionibacterium acnes, and Pseudomonas aeruginosa keratitis with or without endophthalmitis represent the most common indication for ocular enucleation/evisceration in patients with microbial keratitis in a tertiary referral center in Hungary. The incidence of enucleation and evisceration related to mycotic keratitis does not seem to have increased within the last decade. Most frequent preexisting systemic diseases in cases of enucleation and evisceration are hypertension, cardiac disease, diabetes mellitus, and rheumatoid arthritis.